Capacity to Participate: A Case Study of Resident Participation in Somerville, MA - Brandt, Christian. (2018)
Abstract: This thesis aims to better understand residents' capacity to engage in participatory planning processes through a nuanced look at the specific activities residents use and challenges they experience once they are already engaged in participatory processes. This thesis also aims to elaborate the role community groups play in supporting residents' engagement in participatory processes. I explore these challenges in the context of six organized resident groups that have been engaged in decision-making processes in Union Square, Somerville, MA, during the last five years. This thesis finds that residents experienced numerous challenges when participating in decision-making opportunities, pursued a variety of tasks aimed at contending with these challenges, and gained substantial support for their participation from community groups. However, community groups appeared to experience participation differently whether they were legitimized by the City or by the community. Receiving just a little recognition from the City may be worse than receiving none.; Thesis (M.A.)--Tufts University, 2018.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Laurie Goldman.; Committee: Penn Loh.; Keyword: Urban planning.